A Single-Display Groupware Collaborative Language Laboratory - Villalta-Paucar, M (Routledge, 2016)
Language learning tools have evolved to take into consideration new teaching models of collaboration and communication. While second language acquisition tasks have been taken online, the traditional language laboratory has remained unchanged. By continuing to follow its original configuration based on individual work, the language laboratory fails to take advantage of the potential provided by collaborative learning. We propose the use of a language laboratory based on single-display groupware (SDG) for learning vocabulary, grammar, pronunciation, and listening comprehension. By adopting SDG, the language laboratory benefits from the advantages of small group collaborative learning. In this paper, we first describe the design and pedagogical merit of the SDG collaborative language laboratory. We then share the results of a quasi-experimental pre–post comparison study, and use an observation guideline to analyze whether the conditions for collaborative learning have been fulfilled. Based on the results of this study, we conclude that developing pronunciation skills can be more effective when using a collaborative language laboratory versus an individual language laboratory. In addition to this, it can also be concluded that collaborative learning is most effective when accompanied by adequate instructional design. © 2014 Informa UK Limited, trading as Taylor & Francis Group.